Meningkatkan Keterampilan Menulis Karangan Siswa SD melalui Teknik Mind Mapping (Jurnal Motivasi Pendidikan dan Bahasa, 2025)
This research aims to improve the writing skills of elementary school students through the application of mind mapping techniques. The background of this research is based on the low writing ability of students, especially in developing ideas and composing coherent and coherent paragraphs. This study uses the Classroom Action Research (PTK) method which is carried out in two cycles in grade V of elementary school. Each cycle consists of planning, implementation of actions, observation, and reflection. Data collection techniques are carried out through essay writing tests, observation of student activities, and documentation of student work. The results of the study show that the mind mapping technique can help students in systematically compiling ideas before writing, making it easier for them to develop their essays. In the first cycle, only 48% of students achieved the Minimum Completeness Criteria (KKM). After improvements were made in cycle II, completeness increased to 84%. In addition to the increase in writing results, there is also an increase in motivation and active participation of students in the writing learning process. In conclusion, mind mapping techniques have proven to be effective in improving the writing skills of elementary school students. This strategy can be used as an alternative in learning Indonesian to create a more creative, structured, and fun learning atmosphere.